Plant quercetin degradation by gut bacterium Raoultella terrigena of ghost moth Thitarodes xiaojinensis - Liu, Guiqing; Cao, Li; Han, Richou (Frontiers in Microbiology, 2022)
Associated microbes of several herbivorous insects can improve insect fitness. However, the contribution of specific insect gut bacterium to plant toxin toxification for its host fitness remain scarce. Here, a gut bacterium Raoultella terrigena from the ghost moth Thitarodes xiaojinensis larvae was identified. This bacterium grew unhindered in the presence of Polygonum viviparum, which is a natural food for ghost moth larvae but showed significant growth inhibition and toxicity against Spodoptera litura. S. litura reared on artificial diets containing 5%, 15% and 25% P. viviparum powder after 7 days coculture with R. terrigena were found to have shorter larval and pupal durations than on the diets containing P. viviparum powder but without R. terrigena coculture. HPLC analysis revealed that the content of quercetin in mineral medium containing 15% P. viviparum powder after 7 days coculture with R. terrigena was significantly decreased (79.48%) as compared with that in P. viviparum powder without R. terrigena coculture. In vitro fermentation further verified that R. terrigena could degrade 85.56% quercetin in Lucia-Bertani medium. S. litura reared on artificial diets containing 0.01, 0.05 and 0.1 mg/g quercetin after 48 h coculture with R. terrigena were also found to have shorter larval, prepupal and pupal durations, as well as higher average pupal weight and adult emergence rate than on the diets containing quercetin, but without R. terrigena coculture. In addition, R. terrigena was detected in the bud and root tissues of the sterilized P. viviparum, indicating that T. xiaojinensis larvae might acquire this bacterium through feeding. These results demonstrate that the gut bacteria contribute to the degradation of plant toxic molecules to improve the development of herbivorous insects and provide fundamental knowledges for developing effective methods for beneficial insect rearing and pest control.